PENGARUH LITERASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI MELALUI EFIKASI KEUANGAN PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNARS - Laili, Siti Wiladatul; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2022)
The ability to manage financial decisions for future plans is very important for a prosperous life. The purpose of this study was to analyze and examine the effect of Financial Literacy on Investment Decisions Through Financial Efficacy on Students. The population in this study were students of the Faculty of Economics and Business Unars, the sampling technique was determined by Probability Sampling. Data analysis and hypothesis testing in this study used the Structural Equation - Partial Lest Square (PLS-SEM) model. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that financial literacy has a significant effect on financial efficacy, financial literacy has a significant effect on investment decisions, financial efficacy has a significant effect on investment decisions. The results of the indirect effect hypothesis test show that the financial literacy has a significant positive effect variable on investment decisions through financial efficacy.